ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI - Purwa Abhimantra, Wayan; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2016)
Disbursement of loan that is constantly increasing rural bank, requires prioritizing efficiency and effectiveness of the accounting information system to prevent a credit crunch. Rural bank's reliability on infrastructure, development system, experience to judge credit risk, can rated from internal factors in bank itself. The purpose of this research is to testing the effect of user involvement, personal technique ability, top management support, formalitation development system, training and education on accounting information system performance at rural bank in Denpasar City area. The method for collecting sample in this research is using saturated sampling. The amount of rural bank use as sample is 18. The collecting data is using questionnaire. Analysis technique data is using multipple linear regressions analysis. The result of this research indicate that user involvement, personal technique ability, top management support, formalitation development system, training and education positively effecting accounting information system performance. This result also suggesting that user involvement, personal technique ability, top management support, formalitation development system, training and education is suitable for accounting information system performance to work properly.
Keywords: Performance, Accounting Information System, Rural Bank